The Relationship between Information Needs and Preferences for Selecting Printed and Digital Books among Students of the Library and Information Science Study Program Padjadjaran University - Alwannia, Wafa Huwaiza; Nanda, Azarine Nuhaa Callista Luqman; Prijana (Universitas Airlangga, 2025)
Latar belakang: Transformasi digital telah memengaruhi pola akses informasi mahasiswa, termasuk dalam pemilihan format bahan bacaan. Pilihan antara buku cetak dan buku digital tidak hanya didasari oleh kebiasaan, tetapi juga oleh kebutuhan informasi yang kompleks. Dalam konteks ini, Model Krikelas digunakan untuk menjelaskan bagaimana ketidakpastian pengetahuan mendorong pencarian informasi dan preferensi terhadap format bacaan. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara kebutuhan informasi, perasaan sering kekurangan informasi, dan kebingungan dalam memilih sumber belajar dengan preferensi terhadap format bacaan mahasiswa, serta melihat kecenderungan mahasiswa Program Studi Perpustakaan dan Sains Informasi Universitas Padjadjaran dalam memilih format buku untuk keperluan akademik. Metode: Penelitian menggunakan pendekatan kuantitatif dengan metode survei. Responden berjumlah 133 mahasiswa, yang merupakan hasil dari proses pemilihan acak sederhana (simple random sampling) dari populasi yang berjumlah 291 mahasiswa. Data dianalisis menggunakan uji korelasi Pearson sederhana dengan bantuan SPSS. Hasil: Penelitian ini menunjukkan adanya hubungan yang signifikan antara kebutuhan informasi dengan preferensi mahasiswa terhadap format bacaan (nilai korelasi Pearson 0,432). Mahasiswa Perpustakaan dan Sains Informasi Universitas Padjadjaran cenderung memilih buku digital dalam praktik akademik karena kemudahan akses, efisiensi waktu, dan fleksibilitas. Namun, buku cetak tetap dianggap lebih efektif dalam membantu pemahaman materi. Kesimpulan: Mahasiswa cenderung memilih buku digital dalam praktik akademik karena kepraktisan, meskipun buku cetak tetap dianggap lebih efektif dalam pemahaman materi. Preferensi ini menunjukkan strategi adaptif mahasiswa dalam merespons kebutuhan informasi akademik mereka. Background: The digital transformation has influenced how university students access information, including their choice of reading material formats. The preference between print and digital books is no longer merely a matter of habit, but is also driven by increasingly complex information needs. In this context, the Krikelas Model is applied to explain how perceived uncertainty in knowledge triggers information-seeking behavior and shapes preferences toward certain reading formats. Purpose: This study aims to determine the relationship between information needs, the feeling of frequently lacking information, and confusion in selecting learning resources with students’ preferences for reading formats, as well as to explore the tendencies of students in the Library and Information Science Program at Universitas Padjadjaran in choosing book formats for academic purposes. Methods: A quantitative approach was used with a survey method. The respondents consisted of 133 students, selected through a simple random sampling process from a population of 291 students. Data were analyzed using Pearson correlation with the aid of SPSS software. Results: This study shows a significant relationship between information needs and student preferences for reading formats (Pearson correlation value 0.432). Students in the Library and Information Science Program tend to choose digital books for academic activities due to accessibility, time efficiency, and flexibility. However, print books are still perceived as more effective in aiding comprehension. Conclusion: Students tend to prefer digital books in academic practice for their practicality, although print books remain favored for deeper understanding. This preference reflects an adaptive strategy in response to academic information needs.